Preparation method of waxy corn starch-based shear thickening adhesive containing boric acid double-crosslinking structure
The shear thickening glue prepared by crosslinking polyvinyl alcohol with boric acid and adding waxy corn starch is solved, and the problems of complex preparation, high cost and unstable material properties in the prior art are achieved, and green, environmentally friendly and efficient preparation of shear thickening glue is achieved.
Patent Information
- Application Number
- CN202510043714.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
AI Technical Summary
The existing shear thickening glue preparation methods are complex, have high production costs, and may have an impact on the environment and human body. The materials are prone to layering and nanoparticles falling off after long-term placement, resulting in reduced performance.
A polymerization network is formed by cross-linking polyvinyl alcohol and boric acid, and waxy corn starch is added as the dispersed phase. A green shear thickening glue is prepared by chemical double cross-linking reaction of boron ester and physical action of hydrogen bonds.
The production cost is reduced, the production efficiency is improved, the process is simplified, and the prepared shear thickener glue has better environmental protection performance and biocompatibility, and its stability and packaging are also improved.
Smart Images

Figure BDA0005237697740000051 
Figure BDA0005237697740000052 
Figure BDA0005237697740000061
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a shear thickening glue, in particular to a method for preparing a waxy corn starch-based shear thickening glue containing a boric acid double cross-linking structure. Background Art
[0002] Shear thickening materials are a new type of intelligent material that exhibits a thickening effect under the action of shear force. In recent years, shear thickening fluids and their composites have received widespread attention in the fields of protective materials, biomedicine, military equipment, etc. due to their unique rheological properties. When subjected to external forces, the viscosity of the shear thickening fluid will increase rapidly, showing a phase transition from liquid to solid-like state. This property enables it to provide additional protection when it is impacted. However, shear thickening fluids also have some inherent defects. For example, shear thickening fluids are in liquid form under normal conditions, which makes it easy to leak or overflow during packaging and carrying; since shear thickening fluids are a suspension system composed of nano- or micron-sized particles and Newtonian fluids, this system is prone to stratification after long-term storage and nanoparticles are easy to fall off, resulting in a decrease in the performance of the material.
[0003] A new type of shear thickening material based on molecular colloids - shear thickening glue perfectly overcomes the defects of shear thickening liquid. Shear thickening glue is soft and elastic when not under force. Once it is subjected to severe impact, the molecules will quickly lock with each other to form a hard protective layer. When the external force disappears, the material can quickly return to its original soft state. This material is not only easy to encapsulate and carry, but also the colloidal polymers interact with each other in the form of chemical bonds, the properties are more stable, and the problem of nanoparticles falling off is not easy to occur. At present, the preparation methods of shear thickening glue mainly include physical crosslinking method, chemical crosslinking method and temperature control method. These methods promote crosslinking between gel molecules through different means to form a 3D network structure, thereby enhancing its thickening effect. However, the existing shear thickening glue is generally a borosiloxane polymer. The reaction process preparation process is complicated and requires specific raw materials. The preparation and processing process requires specific technology and equipment, which increases production cost and time, and also limits the large-scale production and application of materials, and may have a certain impact on the human body and the environment. Summary of the invention
[0004] In order to solve the above problems, the present invention proposes a method for preparing a waxy corn starch-based shear thickening glue containing a boric acid double cross-linked structure. By using the molecular cross-linking and repulsive dispersion principle, a polymer network formed by cross-linking polyvinyl alcohol and boric acid is used to replace borosiloxane polymers, and waxy corn starch is added as a dispersed phase. A green shear thickening glue is prepared through the synergistic effect of polyvinyl alcohol, boric acid, and waxy corn starch. The preparation method can not only reduce production costs and improve production efficiency, but also has a relatively simple preparation process and better environmental protection performance and biocompatibility.
[0005] The present invention is achieved by the following steps:
[0006] A method for preparing a waxy corn starch-based shear thickening glue containing a boric acid double cross-linked structure comprises the following steps:
[0007] (1) Preparation of PVA aqueous solution
[0008] Dissolving PVA powder in deionized water to prepare a PVA aqueous solution with a concentration of 8 to 12 wt%;
[0009] (2) Preparation of PVA / B cross-linked dispersion
[0010] Prepare a boric acid aqueous solution with a concentration of 0.5-3wt%, then drop the boric acid aqueous solution into the PVA aqueous solution obtained in step (1), place on a magnetic stirrer, stir continuously at room temperature at a speed of 200-500r / min for 30-60min, then adjust the temperature to 60-75°C and heat and stir for 1-4 hours to obtain a PVA / B cross-linked dispersion.
[0011] (3) Preparation of waxy corn starch-based shear thickening gel
[0012] A certain amount of waxy corn starch is added to the PVA / B cross-linked dispersion obtained in step (2) while stirring, and the PVA / B cross-linked solution and the waxy corn starch are fully mixed by stirring to obtain a waxy corn starch-based shear thickening gel.
[0013] Based on the above technical solution, further, in step (1), the degree of polymerization of the polyvinyl alcohol used is 1700-3000, and the degree of alcoholysis is 88%-99%.
[0014] Based on the above technical scheme, further, in step (1), the preparation method of the PVA aqueous solution is: PVA powder is poured into deionized water, stirred and dissolved on a magnetic stirrer, the stirring speed is set to 300-500r / min, and after stirring at room temperature for 0.5-2 hours, the temperature is adjusted to 80-100°C and stirred for 8-12 hours to obtain the PVA aqueous solution; preferably: the stirring speed is set to 500r / min, and after stirring at room temperature for 1 hour, the temperature is adjusted to 80-100°C and stirred for 10 hours.
[0015] Based on the above technical solution, further, in step (2), the volume ratio of the polyvinyl alcohol aqueous solution to the boric acid aqueous solution is 1:0.5 to 1:2, preferably 1:0.5 to 1:1.5.
[0016] Based on the above technical solution, further, in step (2), the boric acid aqueous solution is slowly dripped into the PVA aqueous solution, and the slow dripping is slow dripping drop by drop.
[0017] Based on the above technical scheme, further, in step (2), the boric acid aqueous solution is prepared by adding boric acid into deionized water, placing the solution on a magnetic stirrer, and stirring the solution at room temperature at a speed of 300-500 r / min for 10-20 min to fully dissolve the boric acid solution.
[0018] Based on the above technical solution, further, in step (2), after continuous stirring at room temperature for 30 minutes, the temperature is adjusted to 70° C. and then heated and stirred for 2.5 hours.
[0019] Based on the above technical solution, further, in step (3), the amylopectin content of the waxy corn starch used is greater than 90%.
[0020] Based on the above technical solution, further, in step (3), the mass ratio of the PVA / B cross-linking solution to the waxy corn starch (WCS) is 1:0.5 to 1:2, preferably 1:0.5 to 1:1.5.
[0021] Based on the above technical solution, further, in step (3), the conditions for uniform mixing are: continuous stirring at a speed of 300-600 r / min for 20-60 min.
[0022] The present invention also relates to a waxy corn starch-based shear thickening glue containing a boric acid double cross-linking structure prepared by the preparation method.
[0023] The waxy corn starch-based shear thickening glue containing a boric acid double cross-linked structure can be used in the preparation of flexible protective textiles and can be composited with different types of non-woven fabrics, nanofiber membranes or fabrics.
[0024] A flexible protective textile utilizes the above-mentioned waxy corn starch-based shear thickening glue to be compounded with non-woven fabrics, nanofiber membranes or fabrics prepared from various textile raw materials, and the waxy corn starch-based shear thickening glue is encapsulated to prepare a flexible protective textile with green, environmentally friendly and skin-friendly characteristics.
[0025] Based on the above technical solution, further, the fabric is a woven fabric, such as cotton woven fabric, polyester-cotton woven fabric, polyester woven fabric, etc., which can be a plain or twill weave structure.
[0026] Based on the above technical solution, the fabric is first coated with Ecoflex material. Then, the shear thickening glue is evenly filled and encapsulated between two layers of woven fabric that have been coated with Ecoflex, and the upper and lower layers of fabric are bonded along the edge area using Ecoflex, thereby forming a complete flexible protective fabric structure with shear thickening properties.
[0027] The invention selects polyvinyl alcohol (PVA) and boric acid to prepare a hydrosol-like cross-linked network as a dispersion medium, and waxy corn starch as a dispersed phase, and the two are mixed to prepare a natural environmentally friendly shear thickening glue with chemical and physical double cross-linking and relatively simple processing and preparation process.
[0028] Beneficial effects:
[0029] 1. Made of waxy corn starch, polyvinyl alcohol and boric acid, the raw materials are abundant, renewable, environmentally friendly, biodegradable, non-toxic and biocompatible.
[0030] 2. The process is short, the operation is convenient, the production cost is reduced and the economic benefits are improved.
[0031] 3. The shear thickening glue is prepared by the boron ester chemical double cross-linking reaction and hydrogen bond physical action between PVA, boric acid and waxy corn starch. The shear thickening glue system is not easy to settle, the system is stable, easy to package and carry, and convenient to use.
[0032] 4. The molecular structure of the system is easy to design and can be adjusted and optimized according to specific needs.
[0033] 5. Since shear thickening adhesive can be compounded with fabric, it provides a new material option for flexible textile protection applications and expands the application field.
[0034] Instruction Manual
[0035] Figure 1 This is a stability diagram of the waxy corn starch-based shear thickening gum sample prepared in Example 1.
[0036] Figure 2 This is a stability diagram of the waxy corn starch-based shear thickening gum sample prepared in Example 2.
[0037] Figure 3 This is a stability diagram of the waxy corn starch-based shear thickening gum sample prepared in Example 3.
[0038] Figure 4 This is a stability diagram of the waxy corn starch-based shear thickening gum sample prepared in Example 4.
[0039] Figure 5The schematic diagram of the double cross-linked structure of the shear thickening glue. Boric acid is an inorganic cross-linking agent. PVA and boric acid will form a single cross-linked network structure of boron ester; it will react with the hydroxyl (-OH) in the molecular chain of waxy corn starch to form a chemical double cross-link of P / B / W; PVA and WCS form a physical cross-linked network due to hydrogen bonds.
[0040] Figure 6 This is a physical picture of the sample of the flexible protective textile prepared in Example 5.
[0041] Figure 7 This is a real picture of the softness of the flexible protective textile sample prepared in Example 5. DETAILED DESCRIPTION
[0042] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0043] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are commercially available or can be prepared by conventional methods unless otherwise specified.
[0044] PVA: polyvinyl alcohol, molecular weight (Mn): 84000-89000, alcoholysis degree: 87.0-89.0% (mol / mol), non-volatile matter: ≤2.0%, acetate: ≤0.5%, Chengdu Cologne Chemical Co., Ltd.; waxy corn starch (branched starch content greater than 96%), Shanghai McLean Biochemical Technology Co., Ltd.; boric acid, Shanghai McLean Biochemical Technology Co., Ltd.; Ecoflex material, Smooth-On, USA.
[0045] Example 1 Preparation of waxy corn starch-based shear thickening glue
[0046] Weigh a certain amount of PVA powder and pour it into deionized water to prepare a 10wt% PVA aqueous solution. Place the solution on a magnetic stirrer and stir to dissolve. Set the stirring speed to 300r / min, stir at room temperature for 1 hour, then adjust the temperature to 95℃ and stir until the solution is completely transparent.
[0047] Weigh a certain amount of boric acid powder and pour it into deionized water to prepare a 1.5wt% boric acid aqueous solution, and place it on a magnetic stirrer and stir it at a speed of 300r / min for 10 minutes to fully dissolve it. Then slowly drip the dissolved boric acid aqueous solution drop by drop into the prepared 10wt% PVA aqueous solution to obtain a PVA / B crosslinked dispersion (V PVA :V B=1:1). The dispersion was placed on a magnetic stirrer at a stirring speed of 300r / min. After continuous stirring at room temperature for 30min, the temperature was adjusted to 70°C and heated and stirred for 2.5 hours. A certain mass of waxy corn starch (the mass ratio of PVA / B cross-linked solution to waxy corn starch was 1:1) was added to the prepared PVA / B cross-linked dispersion while stirring at a stirring speed of 500r / min for continuous stirring for 30min. The PVA / B cross-linked solution and waxy corn starch were fully mixed by stirring. The rheological data of the prepared waxy corn starch-based shear thickening glue are shown in Table 1, where γ0 is the critical shear rate, γ′ is the peak shear rate, and η min is the minimum viscosity of shear thickening, η max is the maximum viscosity of shear thickening, and △η is the difference between the maximum viscosity and the minimum viscosity. The prepared P / B / W dispersion was placed at room temperature for two days, and photos were taken to record the changes of the sample dispersion after 1 day and 2 days. The stability results are shown in Figure 1 shown.
[0048] Table 1 Shear thickening data table
[0049]
[0050] In Table 1, the γ0 value is relatively small, which is 100s -1 , indicating that the system has good speed sensitivity and is more likely to undergo shear thickening. The △η value is relatively large, at 149.06Pa.s, indicating that the system has better shear thickening performance. This product is a milky white suspension. As the placement time increases, the liquid surface tilts and extends, indicating that it has a certain fluidity. No stratification occurs after one or two days of placement (see Figure 1 ), indicating that the whole sample system has good stability, which solves the shortcomings of unstable performance and stratification of shear thickening fluid.
[0051] Example 2 Preparation of waxy corn starch-based shear thickening glue
[0052] Weigh a certain amount of PVA powder and pour it into deionized water to prepare a 12wt% PVA aqueous solution. Place the solution on a magnetic stirrer and stir to dissolve. Set the stirring speed to 300r / min, stir at room temperature for 1 hour, then adjust the temperature to 95℃ and stir until the solution is completely transparent.
[0053] Weigh a certain amount of boric acid powder and pour it into deionized water to prepare a 1.5wt% boric acid aqueous solution, and place it on a magnetic stirrer and stir it at a speed of 300r / min for 10 minutes to fully dissolve it. Then slowly drip the dissolved boric acid aqueous solution drop by drop into the prepared 12wt% PVA aqueous solution to obtain a PVA / B crosslinked dispersion (V PVA :V B=1:1). The dispersion was placed on a magnetic stirrer at a stirring speed of 300 r / min. After continuous stirring at room temperature for 30 min, the temperature was adjusted to 70°C and heated and stirred for 2.5 hours. A certain amount of waxy corn starch (the mass ratio of PVA / B cross-linked solution to waxy corn starch was 1:1) was added to the prepared PVA / B cross-linked dispersion while stirring at a stirring speed of 500 r / min for 30 min. The PVA / B cross-linked solution and waxy corn starch were fully mixed by stirring. The rheological data of the prepared waxy corn starch-based shear thickening glue are shown in Table 2, and the stability results are shown in Figure 2 shown.
[0054] Table 2 Shear thickening data table
[0055]
[0056] In Table 2, the γ0 value of Example 2 reaches 251.21s -1 , indicating that the critical shear rate value at which the system begins to significantly shear thicken increases, indicating that the speed sensitivity of the system decreases. The △η value is 8.28Pa·s, reflecting that the viscosity of the system changes slightly, indicating that the viscosity does not increase significantly during the shear process and the shear thickening performance is relatively weak; it also shows that the system has good fluidity at rest or at low shear rates. This product is a milky white suspension. As the placement time increases, the liquid surface tilts and extends, indicating that it has a certain degree of fluidity. No stratification occurred after one or two days of placement (see Figure 2 ), indicating that the whole sample system has good stability, which solves the shortcomings of unstable performance and stratification of shear thickening fluid.
[0057] Example 3 Preparation of waxy corn starch-based shear thickening glue
[0058] Weigh a certain amount of PVA powder and pour it into deionized water to prepare a 10wt% PVA aqueous solution. Place the solution on a magnetic stirrer and stir to dissolve. Set the stirring speed to 300r / min, stir at room temperature for 1 hour, then adjust the temperature to 95℃ and stir until the solution is completely transparent.
[0059] Weigh a certain amount of boric acid powder and pour it into deionized water to prepare a 1.5wt% boric acid aqueous solution, and place it on a magnetic stirrer and stir it at a speed of 300r / min for 10 minutes to fully dissolve it. Then slowly drip the dissolved boric acid aqueous solution drop by drop into the prepared 10wt% PVA aqueous solution to obtain a PVA / B crosslinked dispersion (V PVA :V B=1:1). The dispersion was placed on a magnetic stirrer at a stirring speed of 300 r / min. After continuous stirring at room temperature for 30 min, the temperature was adjusted to 70°C and heated and stirred for 2.5 hours. A certain amount of waxy corn starch (the mass ratio of PVA / B cross-linked solution to waxy corn starch was 1:0.8) was added to the prepared PVA / B cross-linked dispersion while stirring at a stirring speed of 500 r / min for 30 min. The PVA / B cross-linked solution and waxy corn starch were fully mixed by stirring. The rheological data of the prepared waxy corn starch-based shear thickening glue are shown in Table 3, and the stability results are shown in Table 3. Figure 3 shown.
[0060] Table 3 Shear thickening data
[0061]
[0062] In Table 3, the γ0 value of Example 3 reaches 158.49s -1 , indicating that the system has good speed sensitivity and is more prone to shear thickening. The △η value is 6.80Pa·s, reflecting that the viscosity of the system changes slightly, indicating that the viscosity does not increase significantly during the shear process, and the shear thickening performance is relatively weak; it also shows that the system has good fluidity at rest or at low shear rates. This product is a milky white suspension. As the placement time increases, the liquid surface tilts and extends, indicating that it has a certain degree of fluidity. No stratification occurred after one or two days of placement (see Figure 3 ), indicating that the whole sample system has good stability, which solves the shortcomings of unstable performance and stratification of shear thickening fluid.
[0063] Example 4 Preparation of waxy corn starch-based shear thickening glue
[0064] Weigh a certain amount of PVA powder and pour it into deionized water to prepare a 10wt% PVA aqueous solution. Place the solution on a magnetic stirrer and stir to dissolve. Set the stirring speed to 300r / min, stir at room temperature for 1 hour, then adjust the temperature to 95℃ and stir until the solution is completely transparent.
[0065] Weigh a certain amount of boric acid powder and pour it into deionized water to prepare a 1wt% boric acid aqueous solution, and place it on a magnetic stirrer and stir it at a speed of 300r / min for 10 minutes to fully dissolve it. Then slowly drip the dissolved boric acid aqueous solution drop by drop into the prepared 10wt% PVA aqueous solution to obtain a PVA / B crosslinked dispersion (V PVA :V B=1:1). The dispersion was placed on a magnetic stirrer with a stirring speed of 300r / min. After continuous stirring at room temperature for 30min, the temperature was adjusted to 70°C and heated and stirred for 2.5 hours. A certain amount of waxy corn starch (the mass ratio of PVA / B cross-linked solution to waxy corn starch was 1:1) was added to the prepared PVA / B cross-linked dispersion while stirring at a speed of 500r / min for continuous stirring for 30min. The PVA / B cross-linked solution and waxy corn starch were fully mixed by stirring. The rheological data of the prepared waxy corn starch-based shear thickening glue are shown in Table 4, and the stability results are shown in Figure 4 shown.
[0066] Table 4 Shear thickening data table
[0067]
[0068] In Table 4, the γ0 value of Example 4 reaches 251.15s -1 , indicating that the critical shear rate value at which the system begins to significantly shear thicken increases, indicating that the speed sensitivity of the system has decreased. The △η value is 65.95Pa·s, reflecting that the viscosity of the system changes greatly, indicating that the viscosity increases significantly during the shear process and the shear thickening performance is relatively strong. This product is a milky white suspension. As the placement time increases, the liquid surface tilts and extends, indicating that it has a certain degree of fluidity. No stratification occurs after one or two days of placement (see Figure 4 ), indicating that the whole sample system has good stability, which solves the shortcomings of unstable performance and stratification of shear thickening fluid.
[0069] Example 5 Preparation of flexible protective textiles
[0070] Weigh a certain amount of PVA powder and pour it into deionized water to prepare a 10wt% PVA aqueous solution. Place the solution on a magnetic stirrer and stir to dissolve. Set the stirring speed to 300r / min, stir at room temperature for 1 hour, then adjust the temperature to 95℃ and stir until the solution is completely transparent.
[0071] Weigh a certain amount of boric acid powder and pour it into deionized water to prepare a 1.5wt% boric acid aqueous solution, and place it on a magnetic stirrer and stir it at a speed of 300r / min for 10 minutes to fully dissolve it. Then slowly drip the dissolved boric acid aqueous solution drop by drop into the prepared 10wt% PVA aqueous solution to obtain a PVA / B crosslinked dispersion (V PVA :V B=1:1). The dispersion was placed on a magnetic stirrer at a stirring speed of 300 r / min. After continuous stirring at room temperature for 30 min, the temperature was adjusted to 70°C and heated and stirred for 2.5 hours. A certain amount of waxy corn starch (the mass ratio of PVA / B cross-linked solution to waxy corn starch was 1:0.8) was added to the prepared PVA / B cross-linked dispersion while stirring at a stirring speed of 500 r / min for 30 min. The PVA / B cross-linked solution and waxy corn starch were fully mixed by stirring to obtain a waxy corn starch-based shear thickening glue.
[0072] First, Ecoflex material was used to apply a padding process to a 10 cm × 10 cm cotton plain woven fabric (warp and weft density 250 × 250) and cured at room temperature for 4 hours. The amount of liquid applied was about 6.00 g. Subsequently, the three sides of the two layers of coated cotton fabric were bonded with Ecoflex material, and the 15 g of shear thickening glue was filled therein. Then, the fourth side was bonded with Ecoflex material to encapsulate the shear thickening glue therein, thereby forming a complete flexible protective fabric with shear thickening properties (see Figure 6 ), and verify its good flexibility by folding both sides (see Figure 7 ).
Claims
1. A method for preparing a waxy corn starch-based shear thickening glue containing a boric acid double cross-linked structure, characterized in that: The steps include: (1) dissolving PVA powder in deionized water to prepare a PVA aqueous solution with a concentration of 8 to 12 wt %; (2) preparing a boric acid aqueous solution with a concentration of 0.5 to 3 wt %, and then dropping the boric acid aqueous solution into the PVA aqueous solution obtained in step (1), stirring at room temperature at a speed of 200 to 500 r / min for 30 to 60 min, and then heating to 60 to 75° C. and stirring for 1 to 4 hours to obtain a PVA / B cross-linked dispersion; (3) adding waxy corn starch to the PVA / B cross-linked dispersion while stirring, and fully mixing the PVA / B cross-linked solution and the waxy corn starch by stirring to obtain a waxy corn starch-based shear thickening glue containing a boric acid double cross-linked structure.
2. The preparation method according to claim 1, characterized in that: The degree of polymerization of polyvinyl alcohol is 1700-3000, and the degree of alcoholysis is 88%-99%.
3. The preparation method according to claim 1, characterized in that: The amylopectin content of waxy corn starch is greater than 90%.
4. The preparation method according to claim 1, characterized in that: In step (2), the volume ratio of the polyvinyl alcohol aqueous solution to the boric acid aqueous solution is 1:0.5 to 1:
2.
5. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of the PVA / B cross-linking solution to the waxy corn starch is 1:0.5 to 1:
2.
6. The preparation method according to claim 1, characterized in that: In step (3), the conditions for uniform mixing are: continuous stirring at a speed of 300-600 r / min for 20-60 min.
7. The preparation method according to claim 1, characterized in that: In step (1), the preparation method of the PVA aqueous solution is: PVA powder is poured into deionized water, stirred to dissolve, the stirring speed is set to 300-500r / min, stirred at room temperature for 0.5-2 hours, then the temperature is adjusted to 80-100°C and stirred for 8-12 hours to obtain the PVA aqueous solution.
8. The preparation method according to claim 1, characterized in that: In step (2), the boric acid aqueous solution is prepared by adding boric acid into deionized water and stirring for 10-20 minutes to fully dissolve the boric acid aqueous solution.
9. A waxy corn starch-based shear thickening gel having a boric acid double cross-linked structure prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the waxy corn starch-based shear thickening glue containing a boric acid double cross-linked structure as claimed in claim 9 in the preparation of flexible protective textiles.